2021
DOI: 10.1101/2021.01.04.425259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanics of the cellular microenvironment as perceived by cellsin vivo

Abstract: Tissue morphogenesis and repair, as well as organ homeostasis, require cells to constantly monitor their 3D microenvironment and adapt their behaviors in response to local biochemical and mechanical cues1-6. In vitro studies have shown that substrate stiffness and stress relaxation are important mechanical parameters in the control of cell proliferation and differentiation, stem cell maintenance, cell migration 7-11, as well as tumor progression and metastasis12,13. Yet, the mechanical parameters of the microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 50 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Overall, all of the fluorous cyanine dyes display greater solubility in perfluoromethyl cyclohexane than does fluorous rhodamine 3, the current standard for tracking the fluorous phase in biological environments. 24,25 While solubility in perfluorocarbons was our primary interest, we also evaluated the solubility of the cyanine fluorofluorophores in a range of solvents (Figures S4-S7). We found that the fluorous cyanine dyes were well-solubilized in acetone and ethanol.…”
Section: Fluorous Solubilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, all of the fluorous cyanine dyes display greater solubility in perfluoromethyl cyclohexane than does fluorous rhodamine 3, the current standard for tracking the fluorous phase in biological environments. 24,25 While solubility in perfluorocarbons was our primary interest, we also evaluated the solubility of the cyanine fluorofluorophores in a range of solvents (Figures S4-S7). We found that the fluorous cyanine dyes were well-solubilized in acetone and ethanol.…”
Section: Fluorous Solubilitymentioning
confidence: 99%
“…These solvents were selected due to their use as a standard in the fluorous community (PFMC), 2 their prominence as the inner phase of perfluorocarbon nanoemulsions (PFOB and PFD), 8 and their applications toward in vivo force measurements (HFE-7300 and HFE-7700). 25,32 Upon visual inspection, the fluorous-tagged cyanine dyes appeared soluble in all of these solvents. Yet, the absorption spectra revealed that, with the exception of PFOB, F 86 Cy7 (1c) was aggregated in solution (Figure S6).…”
Section: Impact Of Fluorous Solvent On Photophysical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether such measurements are relevant to the time window of morphogenesis still needs to be addressed, since such measurements show how a tissue deforms when applying an exogenous force for a certain time. How these features compare to the magnitude and duration of the endogenously exerted forces is still unclear [9,22,23]. In addition, during such experimental measurements, the applied force typically triggers a large deformation of the material (nonlinear regime).…”
Section: Introductionmentioning
confidence: 99%